Dynamics of pelvis rotation about its longitudinal axis during the golf swing. Issue 5 (4th July 2021) - Takagi, Tokio; Murata, Munenori; Yokozawa, Toshiharu; Shiraki, Hitoshi
ABSTRACT: The purpose of this study was to identify the dynamic factors contributing to pelvis angular velocity about its longitudinal axis (pelvis axial angular velocity) during the golf swing. Thirty-one right-handed skilled golfers (handicap, 3.5 ± 1.8) performed swings with a driver. The kinematic and kinetic data were collected using an optical motion analysis system and two force platforms. The dynamic factors (i.e., joint torque, gravitational force, motion-dependent forces and inertia forces) contributing to pelvis axial angular acceleration were calculated. The present study revealed that the left (lead) hip flexor and adductor torques as well as the right (trail) hip extensor and abductor torques were identified as the main contributors to pelvis axial angular velocity. These hip joint torques contributed not synchronously but sequentially to the pelvis. Although the knee joint torques contributed little to pelvis axial angular velocity directly, the knee joint torques might support the generation of large hip joint torques by regulating joint postures. These findings indicate that the functional coordination of the lower limb segments as well as the magnitude of the joint torques play an important role in rotating the pelvis.